Design and Modeling of an Impulse Continuously Variable Transmission with a Rotational Swashplate - Gang Li̇ (International Journal of Automotive Science and Technology, 2020)
A novel mechanical impulse continuously variable transmission (ICVT) is developed to provide continuously variable speed ratios and smooth acceleration for drivetrains based on a rotational swashplate, and its design principle is illustrated. A swashplate-guide linkage mechanism is used in the ICVT; the speed ratio of the ICVT is changed with the swirl angle of the rotational swashplate. A slider–linkage system, whose mo-tion is controlled by a speed-regulating handle, is used to adjust the swirl angle of the swashplate. A planetary gear system converts the regulated rotational speed of the swashplate to the output shaft of the ICVT. The speed range of the ICVT can be scaled up by coupling planetary gear sys-tems with different speed ratios. Overrunning clutches are used to rectify the rotational speed from the swashplate-guide linkage mechanism to ob-tain the output speed of the ICVT. Since the rotational swashplate can in-troduce large impulse rates of the instantaneous speed ratio, a connecting linkage is used to reduce the impulse rate and unbalanced inertial forces of the ICVT. Experimental tests of the output speed of the ICVT with four guide linkages verify the feasibility of the design and operation perfor-mance of the ICVT.